Zeolite-type adsorbents for separation of hydrocarbon isomers

By using characteristic zeolite adsorbents, the problem of low productivity of the xylene separation process in the prior art is solved, and efficient xylene separation and high purity preparation are achieved.

CN114845806BActive Publication Date: 2025-03-04IFP ENERGIES NOUVELLES +1
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202080088636.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-20
Filing Date
2020-12-18
Publication Date
2025-03-04
Estimated Expiration
2040-12-18

AI Technical Summary

Technical Problem

The prior art has low productivity in liquid phase processes for separation of xylene, especially in simulated countercurrent processes, and it is difficult to effectively improve the separation efficiency of paraxylene.

Method used

The agglomerated zeolite-type adsorbent with a specific Si/Al ratio and particle porosity is used to optimize the crystal size distribution and mechanical strength of the zeolite-type adsorbent to improve the selectivity and mass transfer ability of paraxylene.

Benefits of technology

The separation productivity of xylene is significantly improved, ensuring the preparation of high purity paraxylene, and avoiding the problem of degradation of performance over time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003702228070000211
    Figure BDA0003702228070000211
Patent Text Reader

Abstract

The present invention relates to zeolite adsorbent agglomerates comprising at least one faujasite zeolite containing barium and / or potassium, having a porosity of 25% to 45%, the standard deviation σ of the crystal size distribution in the agglomerates being less than 0.30 μm. The present invention also relates to the use of the zeolite adsorbent agglomerates for separating hydrocarbon mixtures, and to a process for separating hydrocarbon mixtures using the zeolite adsorbent agglomerates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of zeolitic adsorbents in the form of agglomerates comprising faujasite for use in the separation of gaseous or liquid mixtures of aromatic hydrocarbons, more particularly to processes for the separation of xylenes, in particular para-xylene, with improved productivity.

[0002] The present invention further relates to a process for separating gaseous or liquid mixtures of isomers with improved productivity, and more particularly to a process for separating isomers of xylene with improved productivity to produce high purity paraxylene from an aromatic hydrocarbon feed containing isomers having 8 carbon atoms. Background Art

[0003] The use of zeolitic adsorbents consisting of faujasite zeolite (FAU) of type X or Y, which, in addition to sodium cations, also contain barium, potassium or strontium ions, either alone or in a mixture, for the selective adsorption of p-xylene in aromatic hydrocarbon mixtures is well known in the prior art.

[0004] Patents US3558730, US3558732, US3626020 and US3663638 show that zeolite-type adsorbents containing sodium and barium aluminosilicates (US3960774) or sodium, barium and potassium aluminosilicates effectively separate paraxylene present in a C8 aromatic fraction (a fraction containing aromatic hydrocarbons having 8 carbon atoms).

[0005] The adsorbent described in patent US3878127 is used as an adsorbent in a liquid phase process, preferably an adsorbent of a simulated counter-current type process similar to those described in patent US2985589, which is particularly suitable for C8 aromatic fractions.

[0006] The object of the present invention is to improve the productivity of existing processes for the preparation of para-xylene, in particular liquid phase processes, preferably simulated countercurrent type processes for the separation of isomers of xylene from C8 aromatic feeds. It has surprisingly been observed that this productivity can be improved by judicious choice of the characteristics of the zeolitic adsorbent agglomerates used in this type of process.

[0007] Separation in a simulated moving bed should be interpreted in its broad sense herein, i.e., it can be about a simulated countercurrent moving bed or a simulated cocurrent moving bed, or it can involve the so-called "Varicol" process. The Varicol process, proposed by Ludemann-Hombourger (O. Ludemann-Hombourger, R. Nicoud, 2000) and later developed by Novasep, allows for non-synchronized shifting of the inlet and outlet lines (Bailly et al., 2004). In the cycle, the lengths of the four zones can be adjusted by limiting the number of beds required for separation.

[0008] A common feature of this series of processes is to place a zeolite-type adsorbent agglomerate (or more simply "solid adsorbent") in a fixed bed, and the liquid stream in contact with this solid adsorbent is processed by a set of "on-off" valves, or by a single complex valve called a "rotary valve".

[0009] When the active element of the solid adsorbent used as an adsorbent in these processes is zeolite, the zeolite obtained in crystalline form is preferably used in the form of an agglomerate on an industrial scale. These zeolite-type adsorbent agglomerates in the form of laminates, beads or extrudates generally consist of zeolite crystals and a binder. The zeolite crystals form the active element for adsorption, and the binder is intended to ensure the aggregation of the crystals in the form of an agglomerate. The binder also imparts sufficient mechanical strength to the agglomerate to withstand the mechanical stresses it suffers during use in the operating unit. These mechanical stresses are the cause of the formation of "fines", which lead to a decline in performance during the operation of the entire process.

[0010] The process for separating xylene in a simulated moving bed (SMB) has undergone many technical improvements, especially in terms of the liquid distributor plate, but relatively little progress has been made in terms of the intrinsic properties of the solid adsorbent.

[0011] Adsorbents for separating xylene with improved transfer properties for xylene separation are described, for example, in international application WO2008009845, which describes a zeolite X adsorbent with small crystals having a size less than 1.7 μm, the zeolite X adsorbent having a Si / Al atomic ratio such that 1.15 < Si / Al ≤ 1.5, exchanged with barium, and optionally exchanged with potassium in international application WO2014090771, which describes an agglomerated zeolite-type adsorbent having properties optimized especially for the separation of p-xylene from a C8 aromatic fraction. These adsorbents exhibit maximum properties for p-xylene selectivity and mass transfer, while having maximum mechanical strength associated with an optimized adsorption capacity.

[0012] International application WO2018002174 proposes a zeolite-type adsorbent in the form of agglomerates having optimized properties for the separation of gaseous or liquid mixtures of isomers, more particularly the separation of xylenes in the gaseous or liquid phase, in particular the separation of p-xylene from a C8 aromatic hydrocarbon fraction. The zeolite-type adsorbent of the invention particularly exhibits maximum properties of p-xylene selectivity and mass transfer, while having improved strength and high adsorption capacity / adsorbent volume, and is particularly suitable for separation processes of p-xylene in the liquid phase, preferably simulating countercurrent type processes.

[0013] In particular, the application teaches that a strong increase in macroporosity and / or mesoporosity, and thus in particle porosity, is undesirable, since this porosity does not participate in the adsorption capacity. Optimization of diffusion properties and adsorption capacity is obtained by deliberate selection of porosity and tortuosity factor.

[0014] Patent application US 2009 / 0326308 describes a separation process using an adsorbent having a low binder content and containing X-shaped octahedral crystals of nanometer size (typically an average size of less than 500 nm).

[0015] In a process for separating xylenes via adsorption in a simulated moving bed, a zeolite-type adsorbent is contacted with a liquid feed stream (feed mixture) which most often comprises a mixture of C8 hydrocarbons and generally and most often comprises a mixture of xylene isomers, more particularly a mixture of o-xylene, m-xylene, p-xylene, and ethylbenzene.

[0016] By using a zeolite-type adsorbent having a faujasite structure, having a Si / Al ratio between 1.0 and 1.5 (zeolites LSX, MSX, X), exchanged with barium or mostly with barium and a minority with potassium, para-xylene is preferentially adsorbed in the micropores of the zeolite relative to all other hydrocarbon compounds in the feed stream. The adsorbed phase in the micropores of the zeolite becomes enriched in para-xylene compared to the initial mixture forming the feed stream. Conversely, the liquid phase becomes enriched in compounds such as ortho-xylene, meta-xylene, and ethylbenzene in relative proportions greater than the relative proportions characteristic of the initial mixture forming the feed stream.

[0017] The liquid phase is withdrawn from contact with the adsorbent to form a raffinate stream. The adsorbed phase enriched in paraxylene is desorbed by the desorbent stream and withdrawn from contact with the adsorbent to form an extract stream.

[0018] In the process of separating xylenes by adsorption in a simulated moving bed, a solid zeolite-type adsorbent is passed through one or two multistage towers to contact with a liquid stream. A multistage tower is a tower consisting of a plurality of plates arranged along a substantially vertical axis, each plate supporting a bed of granular solids, and different successive beds receiving a throughflow of the series of liquids used in the tower. Between two successive beds there is a liquid distribution device for feeding each bed of granular solids.

[0019] In general, the operation of a column in a simulated moving bed can be described as follows:

[0020] The column comprises at least four zones, and optionally five or six zones, each of which consists of a certain number of consecutive beds and each zone is defined by its position between an inlet line and an outlet line. Typically, a simulated countercurrent unit (SCC) for the production of paraxylene is fed with at least one feed F to be fractionated (a feed mixture of aromatic hydrocarbons consisting of isomers having 8 carbon atoms) and a desorbent D, sometimes called eluent (generally para-diethylbenzene or toluene), and at least one raffinate R (containing the feed product with the lowest selective adsorption and desorption) and an extract E (containing the feed product with the highest adsorption and desorption) are withdrawn from the unit.

[0021] Other inlet and outlet lines can be added to flush the distribution circuit as described in patent US7208651. Since adding these additional flushing flows does not change the operating principle of the SCC unit in any way, for the sake of brevity, we will not include these additional inlet and outlet lines in the process description of the present invention.

[0022] The inlet and outlet lines vary with time, displacing in the same direction by a value corresponding to one bed. As taught in patent US6136198, the displacement of the different inlet or outlet lines can be simultaneous or not. The process according to this second mode of operation is called Varicol.

[0023] Conventionally, four distinct chromatographic zones are defined in a column operated in simulated countercurrent flow (SCC).

[0024] - Zone 1: desorption zone of the most adsorbed product in the feed, located between the injection of the desorbent D and the withdrawal of the extract E.

[0025] Zone 2: desorption zone for the least selectively adsorbed product in the feed, situated between the withdrawal of the extract E and the injection of the feed F to be fractionated.

[0026] - Zone 3: The adsorption zone of the most adsorbed product in the feed, located between the injection of the feed and the withdrawal of the raffinate R.

[0027] Zone 4: the zone situated between the withdrawal of the raffinate R and the injection of the desorbent D.

[0028] In order to increase the productivity of separation processes, the prior art teaches that one way is to improve the bulk transfer into the agglomerates of zeolite-type adsorbents, in particular by reducing the size of the crystals and / or the average size of the agglomerates.

[0029] Prior art literature disclosing processes for drug separation (Gomes et al., (2006), Adsorption, vol. 12, p. 375sqq.) describes a liquid chromatography separation process using agglomerates having a size ranging from a few tens of micrometers up to 100 μm.

[0030] In these processes using very small sized adsorbents, the pressure drop ΔP is very high. Such a level of pressure drop ΔP is not common for xylene separation processes. However, it is surprising to observe that the pressure drop ΔP is not a size criterion. It has a particular influence on the thickness of the adsorber wall and the power of the operating unit.

[0031] Another characteristic of the zeolite-type adsorbent agglomerates is the hydration rate of the agglomerates. The hydration of the zeolite is ensured by adding water to the feed and / or desorbent stream to maintain the desired value, for example, when zeolite X, MSX or LSX is used in a xylene separation process by adsorption in a simulated moving bed, the loss on ignition of zeolite X, MSX or LSX is 4% to 7.7%. When the adsorbent contains zeolite X, MSX or LSX, the amount of water added for such a loss on ignition level is such that the weight content of water in the hydrocarbon effluent (extract or raffinate stream) is most often between 0 ppm and 150 ppm, more often between 40 ppm and 150 ppm.

[0032] However, there is generally always a need to increase the productivity of the process.

[0033] Therefore, a first object of the present invention is to propose a zeolite-type adsorbent in the form of agglomerates with optimized properties for separation of gaseous or liquid mixtures of isomers, more particularly for separation of xylenes in the gaseous or liquid phase, in particular for separation of p-xylene from a C8 aromatic hydrocarbon fraction. The zeolite-type adsorbent agglomerates of the present invention exhibit in particular maximum properties of p-xylene selectivity and mass transfer, while having high mechanical strength and adsorption capacity, and are particularly suitable for liquid phase separation processes of p-xylene, preferably simulating countercurrent type processes.

[0034] For this purpose, the present invention proposes an agglomerated adsorbent, preferably faujasite with an Si / A atomic ratio between 1.00 and 1.50, the particle porosity of which is advantageously between 25% and 45%, allowing the production of high-purity paraxylene with improved productivity while avoiding performance degradation over time. More specifically, the present invention relates to an agglomerated zeolite adsorbent comprising at least one faujasite zeolite (FAU-X) having an Si / Al atomic ratio comprised between 1.00 and 1.50 and preferably comprising barium and optionally potassium, wherein firstly the particle porosity is between 25% and 45%, preferably between 30% and 45%, more preferably between 32% and 45%, further preferably between 35% and 45%, particularly advantageously between 36% and 45%, including endpoints, and secondly the standard deviation σ of the crystal size distribution in the agglomerates is less than 0.30 μm, preferably between 0.05 μm and 0.30 μm, more preferably between 0.05 μm and 0.28 μm, further preferably between 0.1 μm and 0.28 μm, most preferably between 0.1 μm and 0.25 μm, including endpoints. Summary of the invention

[0035] Thus, in a first aspect, the present invention relates to an agglomerated zeolite adsorbent comprising at least one faujasite zeolite (FAU-X) having an Si / Al atomic ratio comprised between 1.00 and 1.50 and comprising barium and optionally potassium, characterized in that firstly the granular porosity of the adsorbent is between 25% and 45%, preferably between 30% and 45%, more preferably between 32% and 45%, further preferably between 35% and 45%, particularly advantageously between 36% and 45%, including endpoints, and secondly the standard deviation σ of the crystal size distribution in the agglomerates is less than 0.30 μm, preferably between 0.05 μm and 0.30 μm, more preferably between 0.05 μm and 0.28 μm, further preferably between 0.1 μm and 0.28 μm, most preferably between 0.1 μm and 0.25 μm, including endpoints.

[0036] In one embodiment, the agglomerated zeolite adsorbent of the present invention comprises zeolite crystals having a number-weighted mean diameter of less than 1200 nm, preferably between 100 nm and 1200 nm, more preferably between 400 nm and 1200 nm, further preferably between 500 nm and 1200 nm, yet further preferably between 550 nm and 1200 nm, most advantageously between 600 nm and 1200 nm, inclusive.

[0037] In another embodiment, the agglomerated zeolitic adsorbent of the present invention is in the form of beads having an average diameter of between 100 μm and 1000 μm, preferably between 100 μm and 600 μm, more preferably between 200 μm and 550 μm, endpoints included.

[0038] In a preferred embodiment, the at least one FAU-X zeolite of the agglomerated zeolitic adsorbent of the present invention has a Si / Al atomic ratio of between 1.05 and 1.50, preferably between 1.05 and 1.40, inclusive, more preferably between 1.10 and 1.40, inclusive.

[0039] In another preferred embodiment of the present invention, in the agglomerated zeolite adsorbent of the present invention, no zeolite structure other than the faujasite structure, preferably no zeolite structure other than the faujasite X structure, is detected by X-ray diffraction.

[0040] Furthermore, preferably, the weight fraction of FAU zeolite, and preferably of FAU-X zeolite, is higher than or equal to 80%, relative to the total weight of the agglomerated zeolitic adsorbent of the invention.

[0041] The agglomerated zeolitic adsorbent of the present invention comprises one or more alkali metal or alkaline earth metal ions, preferably selected from sodium, barium and potassium.

[0042] In a preferred embodiment, the barium content in the agglomerated zeolitic adsorbent of the present invention, expressed as barium oxide (BaO), is higher than 10% by weight, preferably higher than 15% by weight, further preferably higher than 20% by weight, yet further preferably higher than 23% by weight, even higher than 33% by weight, relative to the total weight of the adsorbent, and advantageously the barium content is between 23% and 42% by weight and typically between 30% and 40% by weight, both inclusive, relative to the total weight of the adsorbent.

[0043] In another preferred embodiment, the potassium content of the agglomerated zeolitic adsorbent according to the invention, expressed as potassium oxide (KO), is lower than 25% by weight, preferably between 0 and 20% by weight, more preferably between 0 and 15% by weight, endpoints included, relative to the total weight of the adsorbent.

[0044] In one embodiment of the present invention, the agglomerated zeolite adsorbent of the present invention has a loss on ignition measured at 900° C. according to standard NFEN 196-2 of less than or equal to 7.7%, preferably between 0 and 7.7%, more preferably between 3.0% and 7.7%, further preferably between 3.5% and 6.5%, and advantageously between 4.5% and 6%, both inclusive.

[0045] In another aspect, the present invention relates to the use of an agglomerated zeolitic adsorbent as just described in the following process:

[0046] - separation of the C8 aromatic isomer fraction, in particular xylenes, more in particular p-xylene;

[0047] - separation of substituted toluene isomers, such as nitrotoluene, diethyltoluene, toluenediamine, etc.;

[0048] - separation of cresol;

[0049] -Separation of polyhydric alcohols.

[0050] Finally, in another aspect, the invention relates to a process for separating para-xylene from a fraction of aromatic isomers having 8 carbon atoms, using as para-xylene adsorbent an agglomerated zeolite-type adsorbent as defined previously and more particularly in the remainder of this text.

[0051] According to the present invention, the process for separating paraxylene from the aromatic hydrocarbon isomer fraction having 8 carbon atoms is carried out by adsorption of paraxylene in the presence of a desorbent in the gas phase or liquid phase, preferably in the liquid phase, wherein the desorbent is preferably selected from toluene and para-diethylbenzene.

[0052] In a preferred embodiment, the process for separating paraxylene according to the present invention is a simulated moving bed type process, more preferably a simulated countercurrent type process. DETAILED DESCRIPTION

[0053] The zeolite-type adsorbent of the present invention preferably comprises macropores, mesopores and micropores. "Macropores" means pores with openings greater than 50 nm, preferably between 50 nm and 400 nm. "Mesopores" means pores with openings between 2 nm and 50 nm (excluding the end points). "Micropores" means pores with openings less than 2 nm.

[0054] As indicated previously, the adsorbent of the invention is in the form of an adsorbent having a particle porosity of between 25% and 45%, preferably between 30% and 45%, more preferably between 32% and 45%, further preferably between 35% and 45%, particularly advantageously between 36% and 45%, including endpoints. In addition, the standard deviation σ of the crystal size distribution in the adsorbent is less than 0.30 μm, preferably between 0.05 μm and 0.30 μm, more preferably between 0.05 μm and 0.28 μm, further preferably between 0.10 μm and 0.28 μm, and most preferably between 0.10 μm and 0.25 μm, including endpoints.

[0055] The inventors have unexpectedly found that when the standard deviation σ of the crystal size distribution in the zeolite-type adsorbent is greater than 0.30 μm, a drastic decrease in productivity is observed in a para-xylene separation process, particularly in a liquid phase separation process carried out in a simulated countercurrent moving bed.

[0056] It was also unexpectedly observed that this productivity value reaches a maximum value in the case of values ​​of the standard deviation σ of the crystal size distribution in the zeolite-type adsorbent agglomerates less than 0.30 μm. This standard deviation σ value appears to correspond to an optimized particle porosity. It was also observed in a completely unexpected manner that the particle porosity in the zeolite-type adsorbent agglomerates is inversely proportional to the standard deviation σ of the crystal size distribution. Thus, the more the standard deviation σ is reduced, the more the particle porosity is increased. However, too high a particle porosity leads to completely undesirable effects, such as a loss of adsorption capacity, a loss of mechanical strength, etc.

[0057] As a result, by the present invention, a person skilled in the art desiring maximum productivity will find a compromise between the particle porosity and the standard deviation σ of the crystal size distribution in the zeolitic adsorbent agglomerates.Thus, by the agglomerated adsorbents of the present invention, maximum productivity in xylene separation processes can be obtained.

[0058] Advantageously, the agglomerated zeolitic adsorbent is in the form of beads having a mean diameter of between 100 μm and 1000 μm, preferably between 100 μm and 600 μm, more preferably between 200 μm and 550 μm, endpoints included.

[0059] Preferably, the faujasite zeolite-type adsorbent of the present invention comprises barium and optionally potassium.

[0060] In another embodiment of the invention, the zeolitic adsorbent has a barium content higher than 10%, preferably higher than 15%, more preferably higher than 20%, further preferably higher than 23%, even higher than 33% by weight, expressed as barium oxide (BaO), relative to the total weight of the adsorbent. Advantageously, the barium content is between 23% and 42% by weight, and typically between 30% and 40% by weight, both inclusive, relative to the total weight of the adsorbent.

[0061] In another embodiment of the invention, the zeolitic adsorbent may have a potassium content, expressed as potassium oxide K2O, lower than 25% by weight, preferably between 0 and 20%, more preferably between 0 and 15%, endpoints included, relative to the total weight of the adsorbent.

[0062] In another embodiment of the invention, the total content of alkali metal or alkaline earth metal ions other than barium and potassium, expressed as oxides of alkali metal or alkaline earth metal ions other than barium oxide BaO and potassium oxide K2O, is between 0 and 5% by weight, inclusive, relative to the total weight of the adsorbent.

[0063] Preferably, the zeolite-type adsorbent of the present invention is an adsorbent containing FAU zeolite, which is generally referred to as type X zeolite. "Zeolite X" means a zeolite having a Si / Al atomic ratio between 1.00 and 1.50, preferably between 1.00 and 1.40, both inclusive.

[0064] Among zeolite X, there are two subgroups generally known today, referred to as zeolite LSX and zeolite MSX. Zeolite LSX has a Si / Al atomic ratio of about 1 (i.e., 1.00±0.05), and zeolite MSX has a Si / Al atomic ratio between about 1.05 and about 1.15, excluding the end points.

[0065] In a preferred embodiment of the invention, the zeolite X has a Si / Al atomic ratio between 1.15 and 1.50 (inclusive). In another preferred embodiment, the zeolite X is a LSX type zeolite, having a Si / Al atomic ratio of about 1 (i.e. 1.00±0.05). It is also conceivable that the adsorbent contains a mixture of two or more types of zeolite X such as just defined.

[0066] In a preferred embodiment, the at least one FAU zeolite included in the zeolitic adsorbent agglomerate of the present invention has a Si / Al atomic ratio between 1.00 and 1.50, inclusive; preferably between 1.05 and 1.40, more preferably between 1.10 and 1.40. Preferably, the at least one FAU zeolite is zeolite X.

[0067] In another preferred embodiment, in the zeolitic adsorbent agglomerates of the present invention, no zeolite structure other than the FAU structure, preferably no zeolite structure other than the faujasite X structure, is detectable by X-ray diffraction (known to the skilled person by the abbreviation XRD).

[0068] In another preferred embodiment, the weight fraction of FAU zeolite (preferably, said FAU zeolite is zeolite X) is higher than or equal to 80%, the remainder up to 100% preferably consisting of non-zeolitic phases, relative to the total weight of the adsorbent of the invention.

[0069] The zeolitic adsorbent agglomerates of the present invention may contain a non-zeolitic phase (NZP), i.e. a non-crystalline phase which is substantially inert to adsorption. The crystallinity content (weight fraction of zeolite) of the adsorbent of the present invention can be measured by X-ray diffraction analysis known to the skilled person by the abbreviation XRD.

[0070] Preferably, the zeolitic adsorbent agglomerates of the present invention are in the form of agglomerates, i.e. they are composed of crystalline elements (or crystals) of at least one FAU zeolite (such as the FAU zeolite defined hereinbefore), preferably, the crystalline elements (or more simply "crystals") have a number-weighted average diameter of less than 1200 nm, preferably between 100 nm and 1200 nm, more preferably between 400 nm and 1200 nm, further preferably between 500 nm and 1200 nm, yet further preferably between 550 nm and 1200 nm, most advantageously between 600 nm and 1200 nm, endpoints included.

[0071] Implementation

[0072] The zeolite adsorbent agglomerates of the present invention can be prepared by applying the operating modes known to those skilled in the art, as described in the previously cited documents WO2014090771, WO2018002174, US2009 / 0326308, and selecting and adjusting the synthesis parameters to allow the obtained agglomerates to have the desired values ​​of particle porosity and standard deviation σ.

[0073] The process for synthesizing the zeolitic adsorbent agglomerates of the present invention may, for example, comprise at least the following steps:

[0074] a) agglomerating crystals of at least one zeolite of the FAU-X type, with a binder comprising at least 80% of clay or a mixture of zeolitizable clays, optionally with up to 5% of additives, and with water in an amount allowing the formation of agglomerate material; drying the agglomerates at a temperature between 50° C. and 150° C.; calcining the dried agglomerates at a temperature above 150° C., typically between 180° C. and 800° C., preferably between 200° C. and 650° C., under an oxidizing and / or inert purge gas, in particular using gases such as oxygen, nitrogen, air, dry and / or decarbonated air, optionally dry and / or decarbonated oxygen-depleted air;

[0075] b) zeolizing all or part of the binder by contacting the agglomerates obtained in step a) with an alkaline base solution;

[0076] c) cation exchange of the agglomerates of step a) and / or step b) by contacting with a solution of barium ions and / or potassium ions;

[0077] d) optionally subjecting the agglomerates of step c) to an additional cation exchange by contact with a solution of potassium ions;

[0078] e) washing and drying the agglomerates obtained in step c) or d) at a temperature between 50° C. and 150° C.; and

[0079] f) Activation by heating to a temperature generally between 100 and 400° C., preferably between 200 and 300° C., followed by recovery of the zeolitic agglomerated adsorbent.

[0080] The zeolite crystals that can be used in the above-mentioned synthesis step a) can be advantageously synthesized following known operation modes available in scientific literature or patent literature, as well as on the Internet. In particular, the zeolite crystals can be prepared as described in documents CN1191118C or WO2014090771 or US7812208B2, US2009326308 and US2007224113.

[0081] Parameters which allow the standard deviation σ of the agglomerates of the zeolitic adsorbent according to the invention to be controlled are, for example, related to the type of crystals used in step a), in particular to the size and standard deviation of said crystals, and also to the zeolitization conditions of the agglomeration binder, such as temperature, time, pH and duration of the alkaline zeolitization solution, agitation mode, shear rate, pressure, etc.

[0082] More specifically, "type of crystals used in step a)" means in particular the standard deviation of said crystals which can be controlled, for example, by adjusting the synthesis parameters, and in particular the synthesis temperature, the stirring speed, the shear rate, as described, for example, in documents WO2009081022 or US2009326308.

[0083] The synthesis parameters that allow the porosity of the zeolitic adsorbent agglomerates of the invention to be controlled are also known to the skilled person. In general, these parameters include, but are not limited to: binder percentage, type of agglomeration (by extrusion, atomization, granulation, etc.), humidity level, binder type, zeolitization conditions (temperature, time, pH of the alkaline zeolitization solution, duration, agitation mode, shear rate, pressure, etc.).

[0084] In a preferred embodiment, the synthesis of the zeolitic adsorbent agglomerates according to the invention does not comprise the addition of pore-forming agents, the presence of which may lead in particular to a deterioration of the crystallinity.

[0085] The crystalline elements can also be prepared by seeding and / or adjusting the synthesis operating conditions, such as the SiO2 / Al2O3 ratio, the sodium content, and the basicity of the synthesis mixture.

[0086] The synthesis of FAU zeolite is generally carried out in a sodium medium (Na + The crystalline elements of the FAU zeolite thus obtained contain in most cases even exclusively (only) sodium cations. However, it is still within the scope of the invention to use crystalline elements which have undergone one or more cation exchanges between syntheses carried out in the sodium form.

[0087] The size of the crystalline elements of the FAU zeolite crystals used in step a) and the FAU zeolite in the agglomerates of the present invention is measured under a scanning electron microscope (SEM). As previously mentioned, preferably, the average diameter of the crystals is generally less than 1200nm, preferably between 100nm and 1200nm, more preferably between 400nm and 1200nm, further preferably between 500nm and 1200nm, further preferably between 550nm and 1200nm, most advantageously between 600nm and 1200nm, including endpoints.

[0088] The SEM observations also allow the confirmation of the presence of non-zeolitic phases in the agglomerates, for example non-zeolitic phases comprising residual binder (not converted in the zeolitization step), or any other amorphous phase.

[0089] In this document, in particular for crystalline zeolite elements and zeolite-type adsorbents, the expressions "number-weighted mean diameter" or "size" are used. The measurement methods of these magnitudes are explained later in this specification.

[0090] Agglomeration and shaping (step a) can be carried out using any technique known to the skilled person, such as extrusion, compression, agglomeration on a pan granulator, drum granulator, atomization, and the like.

[0091] The ratios of agglomeration binder (see definition below) and zeolite used are typically those known in the art, ie 5 to 20 parts by weight binder / 95 to 80 parts by weight zeolite.

[0092] The agglomerates obtained from step a), whether in the form of beads, extrudates or other forms, generally have a number-weighted average diameter or length (the longest dimension when it is non-spherical) of between 100 μm and 1000 μm, preferably between 100 μm and 600 μm, more preferably between 200 μm and 550 μm, including end points.

[0093] After step a), for example in the case of extrudates, the finest agglomerates can be removed by cyclones and / or sieving and / or oversized agglomerates can be removed by sieving or crushing.

[0094] The agglomeration binder used in step a) comprises a clay or a mixture of clays, and preferably consists of a clay or a mixture of clays. Preferably, these clays are selected from: kaolin, kaolinite, nacrite, dickite, halloysite, attapulgite, sepiolite, montmorillonite, bentonite, illite and metakaolin, and mixtures of two or more thereof in any proportion.

[0095] For the zeolitization step, the agglomeration binder used in step a) contains at least 80%, preferably at least 90%, more preferably at least 95%, more particularly at least 96% by weight of at least one zeolitizable clay, and may also contain other mineral binders such as bentonite, attapulgite, etc. Zeolitizable clay means a clay or a mixture of clays that can be converted into a zeolitic material (most often by the action of an alkaline base solution). In general, the zeolitizable clay belongs to the kaolin series (e.g. kaolinite, nacrite, dickite, halloysite) and / or metakaolin.

[0096] Among the additives optionally used in step a), these may include any type of silica source known to the skilled person, expert in zeolite synthesis, such as colloidal silica, diatomaceous earth, perlite, fly ash, sand or any other form of solid silica.

[0097] In step a), besides the crystalline elements of the FAU zeolite and the binder, further additives may be used, for example additives intended to promote agglomeration or to improve hardening, and other additives known to the skilled person.

[0098] In particular, if the agglomeration binder contains one or more zeolitizable clays, calcination allows the zeolitizable clay (typically kaolin) to be converted into metakaolin, which can then be converted into zeolites in a zeolitization step (step b). The principle is explained in "Zeolite Molecular Sieves", DW Breck, John Wiley and Sons, New York, (1973), pp. 314-315.

[0099] Zeolitization of the agglomeration binder is carried out using any method currently known to the skilled person and can be carried out, for example, by immersing the product from step a) in an alkaline base solution, generally an aqueous solution, such as an aqueous solution of sodium hydroxide and / or potassium hydroxide.

[0100] As a general rule, the concentration of the alkaline zeolitizing solution is preferably between 0.5 M and 5 M. Preferably, the zeolitizing is carried out under heating at a temperature above ambient temperature and typically at a temperature in the interval 80° C. to 100° C. The duration of the zeolitizing process is generally between a few tens of minutes and a few hours, preferably between about 1 hour and 8 hours.

[0101] Preferably, and in order to ensure complete zeolitization of the binder without deteriorating the crystallinity of the zeolite crystals present, the adsorbent is preferably contacted with a cold sodium hydroxide solution and a stepwise increase in temperature is applied, up to a temperature of 80-100°C.

[0102] Similarly, the concentration of sodium hydroxide may be maintained at the same concentration or it may be increased stepwise to maintain maximum crystallinity of the initial crystals and ensure maximum conversion of the zeolitizable binder.

[0103] The cation exchange steps c) and d) are carried out according to conventional methods known to the skilled person and are most often carried out by contacting the agglomerates from step a) with barium and / or potassium salts, such as barium chloride (BaCl2) and / or potassium chloride (KCl), in aqueous solution at a temperature between ambient temperature and 100°C, preferably between 80°C and 100°C, to quickly obtain a high barium content (expressed as barium oxide), i.e. preferably higher than 10%, more preferably higher than 15%, further preferably higher than 20%, yet further preferably higher than 23%, even higher than 33% by weight, relative to the total weight of the adsorbent.

[0104] Advantageously, the barium content (expressed as barium oxide) is between 23% and 42% by weight, typically between 30% and 40%, both inclusive, relative to the total weight of the adsorbent. Preference is given to operating with a large excess of barium ions relative to the zeolite cations that it is desired to exchange, typically ranging from 10 to 12, advantageously by continuous exchange.

[0105] Before and / or after the exchange with barium (step c), an exchange with potassium (step d) may optionally be carried out. As described above, it is also possible to agglomerate the crystalline elements of the FAU zeolite which already contain barium or potassium ions or barium and potassium ions in step a) (the cations contained in the FAU type starting zeolite, typically sodium cations, are previously exchanged with barium or potassium ions or barium and potassium before step a), and steps c) and / or d) are omitted (or not omitted).

[0106] The cation exchange step is generally followed by washing, preferably with water, and the agglomerates thus obtained are then dried.

[0107] Activation after drying is carried out in a conventional manner using methods known to the skilled person, for example generally at a temperature between 100° C. and 400° C., preferably between 200° C. and 300° C., for a time determined according to the desired water content and loss on ignition, typically for 1 to 6 hours.

[0108] Characterization techniques

[0109] Particle size measurement of zeolite crystals:

[0110] The estimation of the number mean average diameter of the elements (ie crystals) of the FAU zeolite used in step a) and of the elements (ie crystals) of zeolite X contained in the agglomerates is carried out by observation under a scanning electron microscope (SEM).

[0111] In order to estimate the size of the zeolite particles (i.e. crystals) on the sample, a set of images is taken at a magnification of at least 5000 times. The diameter of at least 200 particles is then measured using specialized software, such as the Smile View software from LoGraMi. The accuracy is within the interval of 3%. The histogram formed by the diameter measurements allows the standard deviation σ of its distribution to be determined simultaneously.

[0112] Chemical analysis of zeolite-type adsorbent agglomerates - Si / Al ratio and exchange rate:

[0113] The elemental chemical analysis of the final product obtained after the previously described steps a) to f) can be carried out using different analytical techniques known to the skilled person. Among these techniques, mention may be made of: X-ray fluorescence chemical analysis performed on a wavelength dispersive X-ray fluorescence spectrometer (WDXRF), for example on a Tiger S8 from Bruker, such as described in standard NF EN ISO 12677:2011.

[0114] X-ray fluorescence is a non-destructive spectroscopic technique for determining the elemental composition of a sample using the photoluminescence of atoms in the X-ray domain. The excitation of atoms, generally achieved by an X-ray beam or electron bombardment, generates a specific radiation after the atoms return to the ground state. X-ray fluorescence spectroscopy has the following advantages: it is almost independent of the chemical bonding of the elements, which provides an accurate determination of both qualitative and quantitative. After calibration, the measurement uncertainty obtained for each oxide is routinely less than 0.4% by weight.

[0115] These elemental chemical analyses allow verification of both the Si / Al atomic ratio of the zeolite used in the agglomerates and of the final product obtained after steps a) to f) described previously, as well as the quality of the ion exchange described in step c) and optionally step d). In the description of the present invention, the measurement uncertainty of the Si / Al atomic ratio is ± 5%.

[0116] The quality of the ion exchange is related to the number of moles of sodium oxide Na2O remaining in the zeolite agglomerate after the exchange. More specifically, the exchange rate of barium ions is estimated by evaluating the ratio between the number of moles of barium oxide BaO and the number of moles of the group (BaO+Na2O). Similarly, the exchange rate of barium and / or potassium ions is estimated by evaluating the ratio between the total number of moles of barium oxide + potassium oxide (BaO+K2O) and the total number of moles (BaO+K2O+Na2O). It should be noted that the content of the different oxides is provided in weight percentage relative to the total weight of the anhydrous zeolitic adsorbent.

[0117] Particle size measurement of zeolite-type adsorbents:

[0118] Determination of the number-weighted mean diameter of the zeolitic adsorbent obtained after agglomeration and formation step a) is carried out by analyzing the particle size distribution in a sample of agglomerates by imaging according to standard ISO 13322-2:2006, using a conveyor allowing the sample to pass in front of a camera.

[0119] Subsequently, the number weighted mean diameter is calculated from the particle size distribution by applying standard ISO 9276-2:2001. In this document, for zeolite-type agglomerates, the term "number weighted mean diameter" or "size" is used. For the size range of the agglomerates according to the present invention, the precision is within the interval of 0.01 mm.

[0120] Mechanical strength of zeolite adsorbent:

[0121] The crushing strength of zeolite-type adsorbent beds such as described in the present invention is characterized by Shell Method Series SMS 1471-74 "Determination of Bulk Crushing Strength of Catalysts. Compression-Sieve Method", associated with the "BCS Tester" apparatus sold by Vinci Technologies. This method was originally intended to characterize catalysts between 3 mm and 6 mm, and is based on the use of a 425 μm sieve to allow separation of fines during crushing. The use of a 425 μm sieve is still applicable to particles greater than 1.6 mm in diameter, but must be adapted to the particle size of the agglomerates for which characterization is sought.

[0122] The agglomerates of the present invention are generally in the form of beads or extrudates, generally having a number weighted average diameter or length (i.e., the longest dimension for non-spherical agglomerates) of between 0.2 mm and 2 mm, and in particular between 0.2 mm and 0.8 mm, preferably between 0.4 mm and 0.65 mm, including endpoints. Therefore, a 100 μm sieve is used instead of the 425 μm sieve mentioned in Shell standard SMS1471-74.

[0123] The measurement protocol is as follows: 20 cm 3 The sample was previously sieved with a suitable sieve (100 μm) and previously oven dried at 250°C (instead of 300°C as mentioned in Shel1 standard SMS1471-74) for at least 2 hours and placed in a metal cylinder with a known internal cross section. 3 A bed of stainless steel beads applies increasing forces to this sample in incremental stages in order to achieve a better distribution of the force applied by the piston to the adsorbent agglomerates (for spherical particles with a diameter strictly less than 1.6 mm, beads with a diameter of 2 mm are used). The fine powder obtained at different incremental stages of applied pressure is separated by sieving (a 100 μm sieve is used) and weighed.

[0124] The in-bed crushing strength is determined by the pressure in megapascals (MPa) at which the amount of cumulative fines passing through the screen is 0.5% by weight of the sample. This value is obtained by plotting the mass of fines obtained as a function of the force applied to the adsorbent bed on a graph and interpolating the 0.5% by weight cumulative fines. The in-bed crushing strength is typically between a few hundred kPa and a few tens of MPa, and is generally between 0.3 MPa and 3.2 MPa. The accuracy is routinely less than 0.1 MPa.

[0125] Non-zeolitic phase of zeolite-type adsorbent:

[0126] The percentage of non-zeolitic phase NZP, such as unzeolitized binder or any other amorphous phase remaining after zeolitization, is calculated by the following equation:

[0127] NZP=100-∑(ZP)

[0128] Therein ZP denotes the sum of the amounts of zeolite X fractions in the sense of the present invention.

[0129] The percentage of zeolite X fraction (percent crystallinity) is measured by X-ray diffraction analysis known to the skilled person by the abbreviation XYD. This analysis is carried out on a Bruker equipment and the percentage of zeolite X fraction is evaluated using Bruker's TOPAS software.

[0130] Micropore volume:

[0131] The crystallinity of the agglomerates can also be assessed by measuring their micropore volume by comparing it with a suitable reference (a 100% crystalline zeolite under the same cation treatment conditions, or a theoretical zeolite). This micropore volume is determined by measuring a gas adsorption isotherm (e.g. nitrogen) at the liquefaction temperature of the gas.

[0132] Before adsorption, the zeolite adsorbent was placed in a vacuum (P<6.7x10 -4 The nitrogen adsorption isotherm was then measured at 77 K on a Micromeritics ASAP 2020M device, taking at least 35 measurement points at relative pressures in which the P / P0 ratio was between 0.002 and 1.

[0133] Total volume of macropores and mesopores and particle porosity:

[0134] The volume of macropores Vma and mesopores Vme, the particle density Dp, and the porosity ε of macropores and mesopores p It is measured by mercury intrusion porosimetry. Model 9500 Mercury Porosimeter was used to analyze the pore volume distribution of macropores and mesopores.

[0135] The test method described in the operating manual of the apparatus with reference to standard ASTM D4284-83 consists in placing a pre-weighed sample of the adsorbent (the adsorbent in the form of agglomerates to be tested) of known loss on ignition in a porosimeter cell and, after previous degassing (evacuation pressure of 30 μm of mercury for at least 10 minutes), filling the cell with mercury at a specified pressure (0.0036 MPa) and then applying increasing levels of pressure up to 400 MPa, allowing the mercury to gradually enter the porous network of the sample, using at least 15 pressure levels, up to 0.2 MPa, followed by increments of 0.1 MPa up to 1 MPa, then 0.5 MPa up to 10 MPa, then 2 MPa up to 30 MPa, then 5 MPa up to 180 MPa and finally 10 MPa up to 400 MPa.

[0136] The relationship between the applied pressure and the characteristic dimension of the pore entry threshold (corresponding to the apparent pore diameter) was determined as follows: Using the Laplace-Young equation and assuming a cylindrical pore opening, a contact angle of 140° between mercury and the pore wall, and a mercury surface tension of 485 dynes cm -1. The volume increment ΔVi of the mercury inserted at each pressure level Pi is recorded, allowing the cumulative volume of mercury inserted to be subsequently plotted as a function of the applied pressure V(Pi) or as a function of the apparent diameter of the pores V(li). The value at which the mercury fills all the interparticle voids and after filling is taken as 0.2 MPa, and above this value the mercury is considered to have entered the pores of the adsorbent. The particle volume Vp is then calculated as follows: the volume of the porosimeter cell is subtracted from the cumulative volume of mercury at this pressure (0.2 MPa) and this difference is then divided by the mass of the equivalent anhydrous adsorbent, i.e. the mass of said material corrected for the loss on ignition. The particle density Dp is the reciprocal of the particle volume Vp defined previously.

[0137] The macropore volume Vma of the adsorbent is defined as the cumulative volume of mercury inserted at pressures between 0.2 MPa and 30 MPa, corresponding to the volume contained in pores with an apparent diameter greater than 50 nm. The mesopore volume Vme of the adsorbent is defined as the cumulative volume of mercury inserted at pressures between 30 MPa and 400 MPa. Since the method of measuring the pore volume via mercury intrusion intrusion does not obtain the micropore volume, the total pore volume Vtot, such as measured by mercury intrusion intrusion intrusion, corresponds to the sum of the volumes of macropores Vma and mesopores Vme.

[0138] Therefore, in this document, the macropore volume Vma and the mesopore volume Vme of the zeolite-type adsorbent and their sum (total pore volume Vtot) are expressed in cm 3 g -1 , is measured by mercury intrusion porosimetry and is related to the mass of the sample expressed in anhydrous equivalent (i.e. the mass of the adsorbent corrected for loss on ignition). The particle density Dp is expressed in gcm -3 Expresses and refers to the mass of the sample in terms of anhydrous equivalent.

[0139] Porosity ε of macroporous and mesoporous particles p It is the product of the particle density Dp times the sum of the macropore volume Vma and the mesopore volume Vme:

[0140] εp=Dp x(Vma+Vme)

[0141] Loss on ignition of zeolite adsorbent:

[0142] The loss on ignition is determined in an oxidizing atmosphere by calcining the sample in air at a temperature of 900° C.±25° C. following the operating mode described in standard NF EN196-2 (April 2006). The standard deviation of the measurement is less than 0.1%.

[0143] Example

[0144] Example 1: Preparation of Agglomerates

[0145] As described below, four adsorbents (agglomerates 1, 3, 4 of the present invention and comparative agglomerate 2) were prepared from type X faujasite powder, the average crystal size of which was 0.6 μm. The standard deviations of these crystals were 0.25 μm, 0.30 μm, 0.35 μm and 0.50 μm, respectively.

[0146] Preparation of Agglomerates (of the Invention) 1

[0147] A homogeneous mixture was prepared and 800 g of zeolite crystals (standard deviation 0.25 μm) were mixed with 160 g of kaolin (expressed as calcined equivalent) and 60 g of a compound sold under the trade name Klebosol using an amount of water that allowed the mixture to be extruded. TM The extrudates were dried, calcined (fired clay) at 550° C. for 2 hours under a nitrogen stream and finally crushed to recover agglomerates having a number average diameter of 0.5 mm.

[0148] The agglomerates (20 g) obtained as described above are placed in a reaction mixture adjusted to 85° C.±1° C., 250 mL of a 1 M aqueous sodium hydroxide solution are added thereto, and the reaction medium is left under stirring for 5 hours.

[0149] The agglomerates were then washed with water in 3 consecutive washing operations and the reactor was drained. The washing efficiency was checked by measuring the final pH of the washing water (between 10.0 and 10.5).

[0150] Agglomerates were exchanged by contacting with 0.5M barium chloride solution at 95°C in 4 steps. In each step, the ratio of solution volume to solid mass was 20 mL / g and each exchange lasted 4 hours. Between each exchange, the solid was washed several times to remove excess salt. Agglomerates were then dried at 80°C for 2 hours and finally activated at 250°C for 2 hours under a stream of nitrogen.

[0151] Preparation of Agglomerate 2 (Comparative)

[0152] A homogeneous mixture was prepared and 800 g of zeolite crystals (standard deviation 0.5 μm) were mixed with 145 g of kaolin (expressed as calcined equivalent) and 55 g of a compound sold under the trade name Klebosol using an amount of water that allowed the mixture to be extruded. TM The extrudates were dried, calcined (fired clay) at 550° C. for 2 hours under a nitrogen stream and finally crushed to recover agglomerates having a number average diameter of 0.5 mm.

[0153] The agglomerates (20 g) obtained as described above were placed in a double-jacketed glass reactor regulated at 95°C ± 1°C, 250 mL of a 1.25 M sodium hydroxide aqueous solution were added thereto, and the reaction medium was left under stirring for 4 hours.

[0154] The agglomerates were then washed with water in 3 consecutive washing operations and the reactor was drained. The washing efficiency was checked by measuring the final pH of the washing water (between 10.0 and 10.5).

[0155] Agglomerates were exchanged by contacting with 0.5M barium chloride solution at 95°C in 4 steps. In each step, the ratio of solution volume to solid mass was 20 mL / g and each exchange lasted 4 hours. Between each exchange, the solid was washed several times to remove excess salt. Agglomerates were then dried at 80°C for 2 hours and finally activated at 250°C for 2 hours under a nitrogen stream.

[0156] Preparation of Agglomerates (of the Invention) 3

[0157] A homogeneous mixture was prepared and 800 g of zeolite crystals (standard deviation 0.3 μm) were mixed with 160 g of kaolin (expressed as calcined equivalent) and 60 g of a compound sold under the trade name Klebosol using an amount of water that allowed the mixture to be extruded. TM The extrudates were dried, calcined (fired clay) at 550° C. for 2 hours under a nitrogen stream and finally crushed to recover agglomerates having a number-weighted average diameter of 0.5 mm.

[0158] The agglomerates (20 g) obtained as described above were placed in a double-jacketed glass reactor regulated at 90°C ± 1°C, 250 mL of a 0.9 M sodium hydroxide aqueous solution were added thereto, and the reaction medium was left under stirring for 6 hours.

[0159] The agglomerates were then washed with water in 3 consecutive washing operations and the reactor was drained. The washing efficiency was checked by measuring the final pH of the washing water (between 10.0 and 10.5).

[0160] Agglomerates were exchanged by contacting with 0.5M barium chloride solution at 95°C in 4 steps. In each step, the ratio of solution volume to solid mass was 20 mL / g and each exchange lasted 4 hours. Between each exchange, the solid was washed several times to remove excess salt. Agglomerates were then dried at 80°C for 2 hours and finally activated at 250°C for 2 hours under a nitrogen stream.

[0161] Preparation of Agglomerates (of the Invention) 4

[0162] A homogeneous mixture was prepared and 800 g of zeolite crystals (standard deviation 0.35 μm) were mixed with 150 g of kaolin (expressed as calcined equivalent) and 58 g of a compound sold under the trade name Klebosol using an amount of water that allowed the mixture to be extruded. TM The extrudates were dried, calcined (fired clay) at 550° C. for 2 hours under a nitrogen stream and finally crushed to recover agglomerates having a number-weighted average diameter of 0.5 mm.

[0163] The agglomerates (20 g) obtained as described above were placed in a double-jacketed glass reactor regulated at 90°C ± 1°C, 250 mL of a 1.15 M sodium hydroxide aqueous solution were added thereto, and the reaction medium was left under stirring for 5 hours.

[0164] The agglomerates were then washed with water in 3 consecutive washing operations and the reactor was drained. The washing efficiency was checked by measuring the final pH of the washing water (between 10.0 and 10.5).

[0165] Agglomerates were exchanged by contacting with 0.5M barium chloride solution at 95°C in 4 steps. In each step, the ratio of solution volume to solid mass was 20 mL / g and each exchange lasted 4 hours. Between each exchange, the solid was washed several times to remove excess salt. Agglomerates were then dried at 80°C for 2 hours and finally activated at 250°C for 2 hours under a nitrogen stream.

[0166] Characteristics of Agglomerates 1 to 4

[0167] The mechanical strength (REL) of the agglomerates was characterized using the characterization technique described above and values ​​of 3.2 MPa were obtained for Agglomerate 1 , 3.1 MPa for Agglomerate 2 , 2.9 MPa for Agglomerate 3 and 3.1 MPa for Agglomerate 4 .

[0168] The particle porosity ε in the final agglomerates is listed in Table 1 below: p and the values ​​of the standard deviation σ of the crystals, such as those measured for agglomerates 1 to 4.

[0169] Agglomerate 1 containing BaX crystals showed an average crystal size of 0.79 μm measured for the final agglomerates, Agglomerate 2 containing BaX crystals showed an average crystal size of 0.76 μm measured for the final agglomerates, Agglomerate 3 containing BaX crystals showed an average crystal size of 0.77 μm measured for the final agglomerates, and Agglomerate 4 containing BaX crystals showed an average crystal size of 0.76 μm measured for the final agglomerates.

[0170] The barium exchange efficiency of Agglomerates 1 to 4 was calculated to be 99.0% by elemental analysis of barium and sodium oxide via X-ray fluorescence as described in the Characterization Techniques.

[0171] The BaO content in agglomerates 1 to 4 was 36.2% by weight.

[0172] The loss on ignition measured as previously described was 5.2% ± 0.1%.

[0173] Example 2: Implementation in separation process

[0174] Agglomerates 1, 3 and 4 were used

[0175] Agglomerates 1, 3 and 4 were used to separate p-xylene in a simulated moving bed.

[0176] The unit operated as a simulated moving bed consists of 24 beds of length 1.1 m, with feed injection, desorbent injection, extract withdrawal and raffinate withdrawal. The bed is divided into 4 chromatographic zones, configured as: 5 / 9 / 7 / 3.

[0177] The feed consisted of 50% p-xylene, 14.5% o-xylene, 30.6% m-xylene and 4.9% ethylbenzene. The desorbent was p-diethylbenzene. The temperature was 175° C. and the pressure was 15 bar. The water content was 95 ppm by weight.

[0178] The productivity obtained is listed in Table 1 below. The superficial linear velocity in zone 3 was 1.63 cm s -1 .

[0179] Use Agglomerate 2

[0180] Agglomerate 2 was used to separate p-xylene in a simulated moving bed.

[0181] The unit operated as a simulated moving bed consists of 24 beds of length 1.1 m, with feed injection, desorbent injection, extract withdrawal and raffinate withdrawal. The bed is divided into 4 chromatographic zones, configured as: 5 / 9 / 7 / 3.

[0182] The feed consisted of 50% p-xylene, 14.5% o-xylene, 30.6% m-xylene and 4.9% ethylbenzene. The desorbent was p-diethylbenzene. The temperature was 175° C. and the pressure was 15 bar. The water content was 95 ppm by weight.

[0183] The productivity of paraxylene is 186 kg m -3 h -1 The superficial velocity in zone 3 is 1.63 cm s -1 .

[0184] Table 1 below lists the productivity results for four agglomerated adsorbents.

[0185]

[0186] Table 1

[0187] It is clearly shown that the agglomerates of the present invention allow significant productivity gains to be achieved in para-xylene production processes.

Claims

1. An agglomerated zeolitic adsorbent comprising at least one faujasite FAU-X zeolite having a Si / Al atomic ratio comprised between 1.00 and 1.50 and containing barium and optionally potassium, characterized in that, The adsorbent has a particle porosity between 25% and 45%, inclusive; secondly, the standard deviation σ of the crystal size distribution in the agglomerates is less than 0.30 μm, inclusive, The adsorbent comprises zeolite crystals having a number weighted average diameter of between 100 nm and 1200 nm, inclusive, The adsorbent contains barium in a barium oxide (BaO) content greater than 10% by weight, inclusive, relative to the total weight of the adsorbent, The weight fraction of FAU zeolite is greater than or equal to 80%, relative to the total weight of the adsorbent.

2. An agglomerated zeolitic adsorbent according to claim 1, wherein the adsorbent comprises zeolite crystals having a number weighted average diameter of between 400 nm and 1200 nm, inclusive.

3. Agglomerated zeolitic adsorbent according to claim 1, characterised in that it is in the form of beads having a mean diameter of between 100 μm and 1000 μm, endpoints included.

4. Agglomerated zeolitic adsorbent according to claim 1, wherein said at least one FAU-X zeolite has a Si / Al atomic ratio of between 1.05 and 1.50, inclusive.

5. Agglomerated zeolitic adsorbent according to claim 1 , wherein the adsorbent comprises barium in a barium oxide (BaO) content greater than 15% by weight, inclusive, relative to the total weight of the adsorbent.

6. Agglomerated zeolitic adsorbent according to claim 1 , wherein the adsorbent comprises potassium in a potassium oxide K 2 O content lower than 25% by weight, inclusive, relative to the total weight of the adsorbent.

7. The agglomerated zeolite-type adsorbent according to any one of claims 1 or 2, wherein no zeolite structure other than the faujasite structure is detected by X-ray diffraction.

8. The adsorbent according to claim 1, wherein the weight fraction of FAU zeolite X is greater than or equal to 80%, relative to the total weight of the adsorbent.

9. Use of the adsorbent according to any one of claims 1 to 8 in the following process: - separation of the C8 aromatic isomer fraction; - separation of isomers of substituted toluenes; - separation of cresol; -Separation of polyhydric alcohols.

10. The use according to claim 9 for separating p-xylene from a fraction of aromatic isomers having 8 carbon atoms.

11. Process for separating para-xylene from a fraction of aromatic isomers having 8 carbon atoms, using an agglomerated zeolite-type adsorbent according to one of claims 1 to 8 as para-xylene adsorbent in the liquid or gas phase.

12. Process according to claim 11 for separating p-xylene from a fraction of aromatic hydrocarbon isomers having 8 carbon atoms by adsorption of p-xylene in the liquid phase in the presence of a desorbent.

13. A process according to any one of claims 11 or 12 which is of the simulated moving bed type.

14. Process according to claim 13, which is of simulated countercurrent type.

Citation Information

Patent Citations

  • Adsorbent for adsorption stripping dimethyl benzene and its preparing process

    CN1191118C

  • Process for Preparing Nano Size Zeolites

    US20070224113A1

  • Binderless adsorbents comprising nano-size zeolite x and their use in the adsorptive separation of para-xylene

    US20090326308A1

  • Aromatic hydrocarbon separation by adsorption

    US3558730A

  • Aromatic hydrocarbon separation by adsorption

    US3558732A